A Corpus-Based Analysis of Word 'Ghost' in the Collection of Kenyah Stories - Syarifah, Laily; Febiyani, Febiyani; Anjani, Novira; Munawarah, Siti; Putri, Jairatunnisyah Jaidun; Asih, Yuni Utami; Kalukar, Ventje Jany (Indonesian Journal of EFL and Linguistics, 2024)
To illustrate the concept of ghosts, this research aimed to explain how they were described in Ã`ma LÃ³ngh and Lebuâ€™ Kulit language, the collection of Dayak Kenyah short stories. This research employed a descriptive qualitative method based on figurative language personification theory. Data analysis is conducted using corpus analysis with the AntConc application. This research concluded that there are four categories that employ personification in relation to the term 'ghost' namely the ghosts act like human, the ghosts being described as dying like humans, ghosts can transform into other forms and ghosts being described as animals. The use of personification in these stories allows readers to relate to and believe in the ghost, enhancing the drama and suspense of the story. The ghosts in this research were only described using personification. Further research might investigate ghosts through different theories to see how their appearance can contribute to certain meanings in the stories.